The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1038/srep02850
|View full text |Cite
|
Sign up to set email alerts
|

Effects of radioactive caesium on bull testes after the Fukushima nuclear plant accident

Abstract: We aimed to investigate the effect of chronic radiation exposure associated with the Fukushima Daiichi Nuclear Plant accident on the testis from 2 bulls. Estimated dose of internal exposure in one bull was 0.7–1.2 mGy (134Cs) and 0.4–0.6 mGy (137Cs) and external exposure was 2.0 mGy (134Cs) and 0.8 mGy (137Cs) (196 days). Internal dose in the other was 3.2–6.1 mGy (134Cs) and 1.8–3.4 mGy (137Cs) and external dose was 1.3 mGy (134Cs) and 0.6 mGy (137Cs) (315 days). Sperm morphology and spermatogenesis were with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
41
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
5

Relationship

4
6

Authors

Journals

citations
Cited by 66 publications
(43 citation statements)
references
References 23 publications
0
41
0
Order By: Relevance
“…found that sperm swimming ability was negatively related to radiation levels while Bonisoli-Alquati et al (2011) found that plasma oxidative status could predict sperm performance, further supporting the role antioxidants are known to play in protecting spermatogenesis from the effects of ionizing radiation. Overall, these studies provide convincing evidence that spermatogenesis can be significantly impacted by lowdose radiation and the resulting male infertility may in part explain the smaller population sizes of many species that has been documented for the region (see below).A recent study of bull sperm and testis from the Fukushima region found no evidence for significant histological changes in the testes or sperm morphology (Yamashiro et al 2013) although this study was very preliminary with only 2 bulls from a relatively uncontaminated part of Fukushima represented for the analysis of sperm.Many other cell types and tissues have been shown to be affected by Chernobyl contaminants. Møller, BonisoliAlquati, et al (2013) demonstrated that the frequency of visible tumors on birds was significantly higher in radioactive areas, presumably reflecting elevated mutation rates in somatic tissues.…”
mentioning
confidence: 86%
“…found that sperm swimming ability was negatively related to radiation levels while Bonisoli-Alquati et al (2011) found that plasma oxidative status could predict sperm performance, further supporting the role antioxidants are known to play in protecting spermatogenesis from the effects of ionizing radiation. Overall, these studies provide convincing evidence that spermatogenesis can be significantly impacted by lowdose radiation and the resulting male infertility may in part explain the smaller population sizes of many species that has been documented for the region (see below).A recent study of bull sperm and testis from the Fukushima region found no evidence for significant histological changes in the testes or sperm morphology (Yamashiro et al 2013) although this study was very preliminary with only 2 bulls from a relatively uncontaminated part of Fukushima represented for the analysis of sperm.Many other cell types and tissues have been shown to be affected by Chernobyl contaminants. Møller, BonisoliAlquati, et al (2013) demonstrated that the frequency of visible tumors on birds was significantly higher in radioactive areas, presumably reflecting elevated mutation rates in somatic tissues.…”
mentioning
confidence: 86%
“…Therefore, radiation effects on non-human biota have been a concern since the accident (Callaway, 2013;Schiermeier, 2011a,b), and some radioecological studies have been performed so far (e.g., Fisher et al, 2013;Garnier-Laplace et al, 2011;Kryshev et al, 2012;Strand et al, 2014;Yamashiro et al, 2013). However, further studies are necessary to reach a consistent conclusion regarding whether radiation released during the F1-NPP accident has had an impact on non-human biota.…”
Section: Introductionmentioning
confidence: 99%
“…Although the IAEA generally assumes limited impacts to organisms from dose rates B50 lGy h -1 , there is considerable discussion of these arbitrary thresholds given the lack of sufficient information concerning unknown individual and species variation in sensitivity, the role of multigeneration exposures, and the importance of complex community interactions in determining individual-, population-, and ecosystem-level responses to radiation sources. Recent analyses of organisms inhabiting Chernobyl, Fukushima, and other naturally radioactive regions around the world point to measurable, biologically significant impacts at what are much lower dose rates than those recommended by IAEA (e.g., Mousseau 2009, 2015;Hiyama et al 2012Hiyama et al , 2013Yamashiro et al 2013;Møller et al 2014). Clearly, further research is needed.…”
Section: Resultsmentioning
confidence: 99%